Evaluación de dos abonos orgánicos (humus de lombriz y bionutriente de microorganismo) en banano orito (musa acuminata aa) en el sector San Pedro - Espin Ortega, Edwin Vidal (2022)
This research project was carried out in the San Pedro sector, belonging to the La Maná canton, Cotopaxi province, where the following objectives were set: To study the response of the orito banana to the application of three doses of humus in combination with an organic bionutrient in crop development. Determine the appropriate dose of the products used in the organic fertilization of the orito banana. Carry out a cost analysis of the different treatments under study. A Random Block Design was applied, with three doses of humus in combination with an organic bionutrient, plus a conventional control and an absolute control. The variables evaluated were: plant height (m), plant growth rate (cm/day), pseudostem circumference (cm), number of functional and non-functional leaves and foliar emission, which were calculated at 30, 60 and 90 days of the trial. The results obtained show that the best treatment was T4 (average dose of humus with bionutrient) with a higher plant height at 30 days 1.85m, at 60 days 2.59m and 90 days 3.27m. For the T4 growth rate it reached higher values with 2.37 cm/day, the highest pseudostem circumference was obtained in T4 with 28.01, 42.91 and 66.00 cm in the evaluated ages. Regarding the number of functional and non-functional leaves, T4 showed better responses with 7.71, 9.54 and 12.00 functional leaves at 30, 60 and 90 days. For non-functional leaves, T4 showed better results with 1.33, 1.09 and 0.58 leaves. The highest foliar emission occurred in T4 with 1.36 leaves at the beginning and 6.52 leaves at the end of the investigation. The treatment with profitable production costs was T4 (half dose humus + bionutrient) with USD. 71.23.